Agro-economic efficiency of polycultures of arugula-carrot-lettuce fertilized with roostertree at different population density proportions - Lenilton A. de A. Oliveira; Francisco Bezerra Neto; Aurélio P. Barros Júnior; Maiele L. da Silva; Ocimara F. N. Oliveira; Jailma S. S. de Lima (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aimed to evaluate the agro-economic efficiency of agrosystems of two croppings of arugula (A) and two of lettuce (L) intercropped with carrot (C) under different biomass amounts of roostertree incorporated into the soil and population density proportions between the component crops. The experimental design was a randomized block with four replications, with the treatments arranged in a 4 × 4 factorial scheme. The first factor was made up of the amounts of roostertree biomass incorporated into the soil (10, 25, 40 and 55 t ha-1 on a dry basis) and the second factor by the population density proportions of the component crops in the polycultures (50A-50C-50L%, 40A-50C-40L%, 30A-50C-30L% and 20A-50C-20L% of the population recommended for single crops – PRSC). The agro-economic performance of arugula, carrot and lettuce in polyculture was optimized at 25 t ha-1 of roostertree incorporated into the soil. The population density proportions of arugula, carrot and lettuce of 50A-50C-50L% of the PRSC provided the best agro-economic efficiency to the polyculture.